2021
DOI: 10.1007/s00270-020-02764-3
|View full text |Cite|
|
Sign up to set email alerts
|

Genicular artEry embolizatioN in patiEnts with oSteoarthrItiS of the Knee (GENESIS) Using Permanent Microspheres: Interim Analysis

Abstract: Purpose Planned interim analysis of GENESIS; a prospective pilot study investigating the role of genicular artery embolization (GAE) in patients with mild to moderate osteoarthritis of the knee using permanent microspheres. Methods Thirty-eight patients, median age = 60 (45–83), attended for GAE using 100–300 μm permanent microspheres. All patients had mild to moderate knee OA, resistant to conservative treatments over 6 months. Knee MRI was performed at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 23 publications
5
89
0
2
Order By: Relevance
“…Of the studies that used only permanent embolics, Little et al had one of the lowest rates of discoloration which may be due to placing ice packs on the skin overlying the targeted genicular arteries, resulting in vasoconstriction of cutaneous vessels. 15 Other AEs that have been reported include self-resolving fever in one patient and foot numbness in two patients which resolved with gabapentin.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Of the studies that used only permanent embolics, Little et al had one of the lowest rates of discoloration which may be due to placing ice packs on the skin overlying the targeted genicular arteries, resulting in vasoconstriction of cutaneous vessels. 15 Other AEs that have been reported include self-resolving fever in one patient and foot numbness in two patients which resolved with gabapentin.…”
Section: Methodsmentioning
confidence: 92%
“…11 Major differences in study designs included variation in patient scoring tools. Visual analog scale (VAS) was not used by Landers et al, 14 while the Western Ontario and McMaster Universities Arthritis Index (WOMAC) was not used by Lee et al, 7 Landers et al, 14 and Little et al 15 Instead, both Landers et al 14 and Little et al 15 used the Knee injury and Osteoarthritis Outcome Score (KOOS). Additionally, Embozene was the most used embolic material, but imipenem/cilastatin sodium (IPM/CS) and polyvinyl alcohol have also been used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited published data available suggest that GAE is effective in reducing knee pain from OA (36,37,(41)(42)(43). These studies include single-arm prospective trials, a retrospective case series, and a systematic review.…”
Section: Gae (Current Clinical Evidence)mentioning
confidence: 99%
“…In this issue of CVIR, Little et al [5] showed the results of an interim analysis of a two-year follow-up single-institution prospective cohort study without control group. GENESIS (Genicular artEry embolizatioN in patients with oSteoarthrItiS of the knee) is a safety and feasibility study conducted by a multidisciplinary team that includes orthopedic surgeons and was approved by the National Institute for Health Research.…”
mentioning
confidence: 99%